2014
DOI: 10.1001/jamapediatrics.2014.1694
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the MacArthur Competence Assessment Tool for Clinical Research (MacCAT-CR) for Measuring Children’s Competence to Consent to Clinical Research

Abstract: The MacCAT-CR demonstrated strong psychometric properties. In children aged 9.6 to 11.2 years, consent may be justified when competence can be demonstrated in individual cases by the MacCAT-CR. The results contribute to a scientific underpinning of regulations for clinical research directed toward children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 29 publications
4
107
1
3
Order By: Relevance
“…When the intellectual age cannot be approximated, the chronologic age of 7 is usually the cut-off point [31]. As shown above, new evidence suggests that the majority of children younger than 9 years of age lack the capacity necessary to meaningfully consent [8,9]. These studies are in agreement with a study by Schwartz [32], where the perceptions of children with growth hormone deficiency were assessed.…”
Section: Assentsupporting
confidence: 67%
See 3 more Smart Citations
“…When the intellectual age cannot be approximated, the chronologic age of 7 is usually the cut-off point [31]. As shown above, new evidence suggests that the majority of children younger than 9 years of age lack the capacity necessary to meaningfully consent [8,9]. These studies are in agreement with a study by Schwartz [32], where the perceptions of children with growth hormone deficiency were assessed.…”
Section: Assentsupporting
confidence: 67%
“…Importantly, the new scale judged 37.9 % of the children incompetent to give consent. Not surprising, age predicted competence, and similar to Ondrusek's study, in children younger than 9.6 years of age competence was unlikely at sensitivity of 90 % [9]. The authors suggested that in children aged 9.4-11.2 years, consent can be justified based on tested competence.…”
Section: Measuring Children's Capacity To Consent To Researchsupporting
confidence: 60%
See 2 more Smart Citations
“…We used the MacArthur Competence Assessment Tool for Clinical Research (MacCAT-CR) modified for children (5,17), and a semistructured interview format to assess children's decision-making competence concerning research participation. We also asked the parents to assess their own children's decision-making competence concerning research participation.…”
mentioning
confidence: 99%